Potret Pembelajaran PAI Pasca Pandemi Covid 19 - Nurulita, Dwita; Arifin, Zaenal (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2024)
The COVID-19 pandemic has become a new task for teachers because almost all learning activities are online. And during the post-pandemic period, several things were no longer burdensome for teachers in the teaching process. Every teacher must have a planning and implementation strategy to support the implementation of effective learning. The objectives of this study are 1) To find out post-pandemic PAI learning planning at SMAN 2 Kota Kediri. 2) To determine the implementation of post-pandemic PAI learning at SMAN 2 Kediri City. The research method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. This study's results indicate that teachers still have difficulties adapting to the learning process after the Covid-19 pandemic, so a blended learning strategy is needed to start learning adaptation after the Covid-19 pandemic.